(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Children and adolescents are an age group that requires special attention during the period of increasing tuberculosis morbidity. Significant deterioration of the epidemiologic situation, clinical polymorphism of tuberculosis in children, manifested both by asymptomatic and pronounced picture with extensive destructive changes, low frequency of bacterial excretion requires improvement of methods for diagnosing tuberculosis in children [8, 9,10,11,12,13].